HISTOLOGICAL AND IMMUNOLOGICAL STUDIES ON THE PROTECTIVE EFFECT OF EUCALYPTUS CAMALDULENSIS AGAINST ROUNDUP-INDUCED HEPATOTOXICITY IN FROGS - AWADALLA EA; MOHAMED AAA; ABDELSADIK A (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Roundup (RUP) is a prominent utilized worldwide herbicide. Possible toxicity of RUP is a considerable debate. We studied the possible mode of RUP cytotoxicity and the antitoxic effects of Eucalyptus camaldulensis (EUC) in male of Bufo regularis. Methods: We were analyzed EUC extract scavenging activity and determined the bioactive compounds. In addition, we measured the lipid peroxidation (LPO), histopathological changes, and gene expression in the liver. Frogs were divided into negative control, EUC, RUP, and combined RUP and EUC treated (RUP+EUC) groups. Data were represented as mean±SD and considered statistically significant when p<0.05. Results: Treatment of animals with RUP increased LPO and numerous pathological changes with an increased number of melanomacrophages (MMCs). In addition, RUP-treated group revealed downregulation of different genes associated with immunity and mitochondrial activity. On the other side, RUP+EUC-treated group showed restoration of the normal hepatic structure and ultrastructural integrity for a considerable extent. The current study evidenced immune system dysregulation through recombinant activating gene 1 downregulation and overexpression of CX chemokine receptor type-4 and cytochrome c oxidase subunit I. Conclusion: The current data represent a direct evidence for the toxicity of RUP that experimentally verified by the histopathological changes, elevated LPO, and imbalanced gene expression. Moreover, aggregation of MMCs pointed to the faced immunological challenges due to RUP toxicity. We are emphasizing that uncontrolled use of RUP is potentially hazardous to the living organisms and man. The application of natural antagonists such a plant extract (e.g., EUC) can reduce biological toxicity.